Architecture and Techniques for Diagnosing Faults in IEEE 802.11 Infrastructure Networks - Adya, Atul; Bahl, Victor; Chandra, Ranveer; Qiu, Lili (ACM MobiCom, 2004)
The wide-scale deployment of IEEE 802.11 wireless networks has generated significant challenges for Information Technology (IT) departments in corporations. Users frequently complain about connectivity and performance problems, and network administrators are expected to diagnose these problems while managing corporate security and coverage. Their task is particularly difficult due to the unreliable nature of the wireless medium and a lack of intelligent diagnostic tools for determining the cause of these problems. This paper presents an architecture for detecting and diagnosing faults in IEEE 802.11 infrastructure wireless networks. To the best of our knowledge, ours is the first paper to address fault diagnostic issues for these networks. As part of our architecture, we propose and evaluate a novel technique called Client Conduit, which enables bootstrapping and fault diagnosis of disconnected clients. We describe techniques for analyzing performance problems faced in a wireless LAN deployment. We also present an approach for detecting unauthorized access points. We have built a prototype of our fault diagnostic architecture on the Windows operating system using off-the-shelf IEEE 802.11 cards. The initial results show that our mechanisms are effective; furthermore, they impose low overheads when clients are not experiencing problems.